The impact of al-Insyā al-‘Arabī al-Taḥrīrī on the efficiency of al-Khiṭābah al-‘Arabīyah for female students (Case Study at The Islamic Boarding School of Darussalam Gontor For Female in First Campus) - Yoke Suryadarma; Rohmatin Lil Alamin (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2020)
The Islamic boarding school of Darussalam Gontor (PMDG) is well-known for being an educational institute that uses both Arabic and English in the educational curriculum. One of the Arabic subjects studied in it is al-Insyā al-‘Arabī al-taḥrīrī, which aims to raise students' language proficiency in the field of Arabic writing. And al-khiṭābah al-‘Arabīyah, which is an important activity in raising students’ language proficiency in the field of Arabic speech. This research wanted to explore the effect of al-Insyā al-‘Arabī al-taḥrīrī on al-khiṭābah al-‘Arabīyah for female students, the second grade of the Islamic boarding school of Darussalam Gontor for Female in First Campus, in order to obtain an answer about the influence of the ability of the Arabic written skill on female students’public speaking efficiency or lack of influence. This research is a field research in the form of a quantitative study. The data collection method used is the test method and written documents. The method of data analysis is statistical analysis and product-moment correlation. The result of this research indicated the absence of the influence of al-Insyā al-‘Arabī al-taḥrīrī on al-khiṭābah al-‘Arabīyah of female students. This can be seen from the statistical analysis that the result is 0.207 smaller than the value of the table r, which is (0.213).